Effect of transcranial direct current stimulation on postpartum depression: A study protocol for a randomized controlled trial - Sun, Weiming; Kang, Xizhen; Dong, Xiangli; Zeng, Zijian; Zou, Qing; Su, Meixiang; Zhang, Ke; Liu, Guanxiu; Yu, Guohua (Frontiers in Psychology, 2023)
Postpartum depression (PPD) is a complex combination of physiological, emotional, and behavioral alterations associated with postpartum chemical, social, and psychological variations. It does harm to the relationship between family members, which could last for years. However, standard depression treatments are not ideal for PPD, the outcomes of these treatments are debatable. Transcranial direct current stimulation (tDCS) is an emerging technology to provide patients with PPD a safe and non-pharmacological treatment. tDCS can relieve depression by directly stimulating the prefrontal cortex through the excitatory effect of the anode. It may also ease depression indirectly by promoting the production and release of neurotransmitters GABA. The Mechanism of tDCS makes it an ideal therapeutic approach to treat PPD, although it has not been widely used and its effect has not been evaluated systematically and effectively. A double-blind randomized controlled trial will be conducted involving 240 tDCS-naive patients with PPD to be divided into 2 groups randomly. One group will receive routine clinical treatment and care with active-tDCS, the other group will receive routine clinical treatment and care with sham-tDCS. Each group of patients will receive a 3-week intervention during which they will receive 20 minutes of active or sham tDCS six days per week. Montgomery-Åsberg Depression Rating Scale will be administered before the intervention as baseline and on each weekend throughout the intervention phase. Before and after the intervention, the Perceived Stress Scale as well as the Positive and Negative Affect Schedule will be evaluated. Side effects and abnormal reactions will be recorded during each treatment. As antidepressants are banned in the study, the results are not affected by drugs and are more accurate. Nonetheless, this experiment is conducted in a single center as a small sample experiment, therefore future studies are necessary to confirm the effectiveness of tDCS on PPD.